2004
DOI: 10.1074/jbc.m312868200
|View full text |Cite
|
Sign up to set email alerts
|

Rap1-induced p38 Mitogen-activated Protein Kinase Activation Facilitates AMPA Receptor Trafficking via the GDI·Rab5 Complex

Abstract: Recent evidence has emphasized the importance of p38 mitogen-activated protein kinase (MAPK) in the induction of metabotropic glutamate receptor (mGluR)-dependent long term depression (LTD) at hippocampal CA3-CA1 synapses. However, the cascade responsible of mGluR to activate p38 MAPK and the signaling pathway immediately downstream from it to induce synaptic depression is poorly understood. Here, we show that transient activation of group I mGluR with the selective agonist (S)-3,5-dihydroxyphenylglycine (DHPG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
198
2
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 166 publications
(217 citation statements)
references
References 50 publications
16
198
2
1
Order By: Relevance
“…The demonstration that p38MAPK may play an important role in receptor endocytosis is not new. Several articles have shown that p38MAPK regulates Rab5 proteins and its effectors (21)(22)(23). Rab5 proteins are essential in regulating the endocytosis of numerous receptors.…”
Section: Discussionmentioning
confidence: 99%
“…The demonstration that p38MAPK may play an important role in receptor endocytosis is not new. Several articles have shown that p38MAPK regulates Rab5 proteins and its effectors (21)(22)(23). Rab5 proteins are essential in regulating the endocytosis of numerous receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Available evidence suggests that of the two group I mGluRs, mGluR5 is responsible for mediating LTD induced by application of DHPG Faas et al, 2002;Huang et al, 2004) (but see Volk et al, 2006) as well as by PP LFS (Faas et al, 2002). In addition to the anatomical localization of mGluR5 at postsynaptic sites, the importance of postsynaptic mechanisms in the induction and expression of mGluR LTD is supported by experiments using postsynaptic injection of G-protein inhibitors (Watabe et al, 2002;Huang et al, 2004), or endocytosis and protein synthesis inhibitors that prevent glutamate receptor internalization (Snyder et al, 2001;Xiao et al, 2001), as well as experiments assessing changes in presynaptic release directly (Zhang et al, 2006). Intriguingly, these mechanisms may be different in neonatal hippocampus, with mGluR LTD relying on large presynaptic changes (Nosyreva and Huber, 2005).…”
Section: Postsynaptic Expression Of Group I Mglurs and Induction Sitementioning
confidence: 99%
“…The siRNA sequence against Rab4A (sense 5Ј-GCCAGAACAUUGUGAUCAUd(TT)-3Ј) was kindly provided by M. Cormont (Faculté de Médecine de Nice, Nice, France). The siRNAs against Rab6A/AЈ (Del Nery et al, 2006) and against Rab5A were published previously (Huang et al, 2004), whereas the siRNAs against RCP and Rip11 were described by Peden et al (2004). Cells were transfected with the siRNAs, by using Lipofectamine 2000 (Invitrogen) according to the manufacturer's instructions.…”
Section: Rna Interferencementioning
confidence: 99%